Different Effects of Leucine Supplementation and/or Exercise on Systemic Insulin Sensitivity in Mice - Jiang, Xiaofan; Zhang, Yuwei; Hu, Weichao; Liang, Yuxiu; Zheng, Liang; Zheng, Juan; Wang, Baozhen; Guo, Xin (Frontiers in Endocrinology, 2021)
Objective Obesity-related diseases such as diabetes, hypertension, dyslipidemia, and cardiovascular diseases have increased due to the obesity epidemic. Early intervention for obesity through lifestyle and nutrition plays an important role in preventing obesity-related diseases. Therefore, the purpose of this study is to explore the role of leucine and exercise in adiposity, systemic insulin resistance, and inflammation to provide theoretical and guiding basis for the early prevention and treatment of obesity. Methods C57BL/6J male mice were randomly divided into HFD group or LFD mice group. After 9 weeks, glucose tolerance test (GTT) was performed to detect their systemic insulin sensitivity. Starting from week 10, mice were divided into 8 groups and treated with moderate exercise or/and 1.5% leucine. At week 13, systemic insulin sensitivity was detected by GTT. At week 14, mice were dissected to analyze adiposity and inflammation. Results In LFD mice, exercise significantly increased systemic insulin sensitivity by increasing GLUT4 expression in muscle and decreasing adiposity through increasing AMPK phosphorylation in adipose tissue. In HFD mice, the simultaneous intervention of exercise and leucine increases systemic insulin sensitivity by reducing liver and adipose tissue inflammation via decreasing NFkB p65 phosphorylation, and increasing the expression of adiponectin in adipose tissue. Conclusion There are different mechanisms underlying the effects of exercise and leucine on insulin resistance and inflammation in LFD mice or HFD mice.